(untitled) (Journal of the College of Basic Education, 2025)
The research aims to identify the effect of the Neale model on the acquisition of geographical concepts among fifth grade primary school students. The research was conducted in Baghdad, and the research community was defined as fifth-grade primary school students in the Baghdad Education Directorate/Al-Rusafa II. The sample consisted of (60) students distributed equally into two groups, one experimental and the other control. I was rewarded on variables (chronological age and intelligence), The researcher prepared (24) teaching plans for the experimental group according to the (Neale) model and (24) teaching plans for the control group according to the prevailing method. The researcher also prepared a test to acquire geographical concepts consisting of (36) objective paragraphs. After verifying its validity and reliability and extracting its psychometric properties, it was applied at the end of the experiment to the main research sample. Using the T-test for two independent samples, The results showed that the students in the experimental group outperformed the students in the control group. The researcher made some recommendations and suggested some proposals.